2012
DOI: 10.1088/1748-6041/7/4/045005
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun nanostructured chitosan–poly(vinyl alcohol) scaffolds: a biomimetic extracellular matrix as dermal substitute

Abstract: Electrospinning is a versatile technique to make biomimetic and nanostructured scaffolds for skin tissue engineering. In this study we have electrospun and characterized chitosan (C)-poly(vinyl alcohol) (PVA) blend nanofibers as dermal substitutes and compared with 2D C-PVA films. The in vitro characterization of the C-PVA nanofibers and 2D films were evaluated using mouse 3T3 fibroblast cells and our results demonstrated that the cells adhered and proliferated on the surface of C-PVA nanofibers. In our animal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
56
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(62 citation statements)
references
References 45 publications
(56 reference statements)
0
56
0
Order By: Relevance
“…However, histological analysis usually reveals that the wound healing process has been stimulated more in nanofiber-treated groups (55,56). The addition of growth factors to the nanofibers usually accelerates wound closure compared to control nanofiber-treated groups, as would be expected (52,57).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…However, histological analysis usually reveals that the wound healing process has been stimulated more in nanofiber-treated groups (55,56). The addition of growth factors to the nanofibers usually accelerates wound closure compared to control nanofiber-treated groups, as would be expected (52,57).…”
Section: Discussionmentioning
confidence: 92%
“…Tissue engineering has resulted in the gener- ation of various scaffolds to treat excisional wounds and promote wound healing. Chitosan has shown promise in the form of chitosan hydrogels and chitosan acetate bandages, as well as chitosan-(polyvinyl alcohol) nanofibers (50)(51)(52). Although the main purpose of this study was to determine if NF wound dressings could treat S. aureus-induced infections, the effects of the NF and CF wound dressings on wound closure were also investigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lin et al [60] have reported on incorporation of chitosan into dilute PVA solution and its effect on the blend viscosity and hence improved uniformity of the resulting nanofibres. Recently, electrospun PVA/chitosan scaffolds including growth factors have been produced to address cell attachment and proliferations for accelerated wound healing [59,61,62].…”
Section: Introductionmentioning
confidence: 99%
“…As a unique cationic polysaccharide, chitosan has outstanding biocompatibility, bioadhesion, and biodegradability. There are many methods of introducing chitosan onto synthesized polymers such as alkaline hydrolysis followed by grafting-coating (Lao, Tan, Wang, & Gao, 2008;Sahoo, Sasmal, Nanda, Phani, & Nayak, 2010), layer-by-layer assembly (Zhu, Gao, He, Liu, & Shen, 2003), photo-initiated grafting (Zhu, Zhao, & Ma, 2009), and blending (Cooper, Bhattarai, & Zhang, 2011;Sundaramurthi, Vasanthan, Kuppan, Krishnan, & Sethuraman, 2012). Besides these methods, freeze-drying chitosan solution could also introduce chitosan to the scaffolds (Zhao, Han, Chen, et al, 2012a).…”
Section: Introductionmentioning
confidence: 99%